Drawn out of the shadows: Surveying secretive forest species with camera trap distance sampling. Issue 5 (30th March 2020) - Bessone, Mattia; Kühl, Hjalmar S.; Hohmann, Gottfried; Herbinger, Ilka; N'Goran, Kouame Paul; Asanzi, Papy; Da Costa, Pedro B.; Dérozier, Violette; Fotsing, Ernest D. B.; Beka, Bernard Ikembelo; Iyomi, Mpongo D.; Iyatshi, Iyomi B.; et al.
Abstract: With animal species disappearing at unprecedented rates, we need an efficient monitoring method providing reliable estimates of population density and abundance, critical for the assessment of population status and trend. We deployed 160 camera traps (CTs) systematically over 743 locations covering 17, 127 km 2 of evergreen lowland rainforest of Salonga National Park, block South, Democratic Republic of the Congo. We evaluated the applicability of CT distance sampling (CTDS) to species different in size and behaviour. To improve precision of estimates, we evaluated two methods estimating species' availability ( 'A' ) for detection by CTs. We recorded 16, 700 video clips, revealing 43 different animal taxa. We estimated densities of 14 species differing in physical, behavioural and ecological traits, and extracted species‐specific availability from available video footage using two methods (a) 'ACa' (Cappelle et al. [2019] Am . J . Primatol ., 81, e22962) and (b) 'ARo' (Rowcliffe et al. [2014] Methods Ecol . Evol . 5, 1170). With sample sizes being large enough, we found minor differences between ACa and ARo in estimated densities. In contrast, low detectability and reactivity to the camera were main sources of bias. CTDS proved efficient for estimating density of homogenously rather than patchily distributed species. Synthesis and applications. Our application of camera trap distance sampling (CTDS) to a diverse vertebrate community demonstrates the enormous potential of this methodology for surveys of terrestrial wildlife, allowing rapid assessments of species' status and trends that can translate into effective conservation strategies. By providing the first estimates of understudied species such as the Congo peafowl, the giant ground pangolin and the cusimanses, CTDS may be used as a tool to revise these species' conservation status in the IUCN Red List of Threatened Species. Based on the constraints we encountered, we identify improvements to the current application, enhancing the general applicability of this method. Abstract : Our application of camera trap distance sampling (CTDS) to a diverse vertebrate community demonstrates the enormous potential of this methodology for surveys of terrestrial wildlife, allowing rapid assessments of species' status and trends that can translate into effective conservation strategies. By providing the first estimates of understudied species such as the Congo peafowl, the giant ground pangolin and the cusimanses, CTDS may be used as a tool to revise these species' conservation status in the IUCN Red List of Threatened Species. Based on the constraints we encountered, we identify improvements to the current application, enhancing the general applicability of this method. Résumé: Avec des espèces animales disparaissant à un rythme sans précédent, nous avons besoin d'une méthode de suivi efficace fournissant des estimations fiables de la densité et de l'abondance des populations, essentielles pour l'évaluation de l'état et des tendances des populations. Nous avons déployé 160 pièges photographiques (camera traps) systématiquement sur 743 emplacements couvrant 17, 127 km 2 de forêt pluviale au parc national de la Salonga, bloc sud, République Démocratique du Congo. Nous avons évalué l'applicabilité du camera trap distance sampling (CTDS) à des espèces de tailles et de comportements différents. Pour améliorer la précision des estimations, nous avons évalué deux méthodes d'estimation de la disponibilité des espèces (availability 'A' ) pour la détection par des camera traps. Nous avons enregistré 16, 700 clips vidéo, révélant 43 taxons d'animaux différents et avons estimé les densités de 14 espèces différentes en termes de caractéristiques physiques, comportementales et écologiques, en calculant la disponibilité spécifique à l'espèce à partir des séquences vidéo disponibles en utilisant deux méthodes (1) 'ACa' (Cappelle et al. [2019] Am. J. Primatol., 81, e22962) et (2) 'ARo' (Rowcliffe et al. [2014] Methods Ecol. Evol ., 5, 1170). Les tailles d'échantillon étant suffisamment grandes, nous avons trouvé des différences mineures entre ACa et ARo dans les densités estimées. En revanche, la faible détectabilité et la réactivité à la caméra étaient les principales sources de biais. Le CTDS s'est avéré efficace pour estimer la densité d'espèces réparties de façon homogène plutôt que celle des espèces inégalement réparties. Synthèse et applications. Notre application du camera trap distance sampling (CTDS) à une communauté diversifiée de vertébrés démontre l'énorme potentiel de cette méthodologie pour les études sur la faune terrestre, permettant des évaluations rapides de l'état et des tendances des populations d'espèces qui peuvent se traduire par des stratégies de conservation efficaces. En fournissant les premières estimations d'espèces sous‐étudiées comme le paon du Congo, le pangolin géant et les mangoustes du genre Crossarchus, le CTDS peut être utilisé comme outil pour réviser l'état de conservation de ces espèces dans la liste rouge des espèces menacées de l'UICN. Sur la base des contraintes rencontrées, nous identifions des améliorations à l'application actuelle, renforçant l'applicabilité générale de cette méthode.